Finite element analysis of trapezoidal web beam to column end plate connection - Tiew, Lee Yin (2010)
Most structures especially the conventional steel buildings are usually using the simple design and rigid design methods. However, the actual behaviour is known to fall between these two extreme categories. The use of partial strength connections has been encouraged by studies on the matter. It is proven that it reduces the steel weight in use and thus save the overall construction cost. This project is to analyze the behaviour of trapezoidal web beam profiled to the end plate connection. Comparison between the effect of trapezoidal web beam profiled to end plate connection and stiffener is made to predict the strength, stiffness and rotational capacity of the connections. Previous research shows that the trapezoidal web beam profiled will minimize the need of stiffeners. Six models have been analyzed in this project by using LUSAS 14.0 by various type of beam. The dimension of beam is 150 x 200 x 1600 mm whereas for column is 200 x 200 x 1800 mm. The dimension for the end plate stiffener provided is 95 x 95 x 10 mm. Linear analysis is performed to obtain the deformed mesh, maximum stress and strain under axial load. In addition, a non-linear contact analysis is also done to obtain the relationship of the load-deflection at contact surfaces. The results show that the trapezoidal web beam profiled with end plate stiffener and extended end plate connection provide highest strength compared to others and with least deflection under loads.